It's Personal, (Not) Personnel : leadership lessons for the battlefield and the boardroom - Campbell, Rob (Ascent Audio, 2019)
There has never been a more important time-in corporate America and in the American military-for leaders, at all levels, to understand how to invest in people. This book teaches you to do just that. Written by a twenty-seven-year army colonel, veteran, and leader of more than 5,000 troops in the 1st Brigade of the 101st Airborne Division, It's Personal, Not Personnel offers true stories and practical frameworks you can apply to the people in your organization and on your team. Whether from lack of will, experience or training, many leaders pay lip service to investing in people. Instead, they manage them on spreadsheets and in HR-focused software applications without personal consideration, failing to truly know them, care for them or establish healthy, fulfilling environments in which they can work and serve. Those appointed to guide and delegate often miss the opportunity to create a people-centric environment where productivity and efficiency will improve. It's less about making mechanics, IT managers, or soldiers better at their trade, and it's more about making people better people. Explore the intricacies of personal connection in the workplace by following Rob Campbell through his own experiences leading large teams in high-stakes work, and then learn to apply those insights to your own work as a leader.